Seleksi Penerimaan Desainer Grafis Dalam Sistem Pendukung Keputusan dengan Menerapkan Metode OCRA - Amin, Muhammad; Hutahaean, Jeperson (Journal of Informatics Management and Information Technology, 2024)
In the current digital era, the demand for skilled graphic designers is increasingly high. The selection process for graphic designers often requires complex evaluations with various criteria, which can lead to subjectivity in decision-making. This research aims to develop a Decision Support System (DSS) using the Operational Competitiveness Rating Analysis (OCRA) method to simplify and improve the accuracy of the graphic designer selection process. The OCRA method is chosen for its ability to handle multi-criteria decision-making problems with different weights. The development of this DSS involves identifying and evaluating five main criteria in the selection of graphic designers, namely: education, work experience, design quality, creativity and innovation, and experience working in various institutions. Each criterion has a different assessment weight according to its level of importance. This system is designed to reduce subjectivity by providing objective preference values based on OCRA calculations. This research aims to develop a DSS in the selection of graphic designers using the OCRA method. The OCRA method is chosen for its ability to address multi-criteria decision-making problems with different weights. The proposed DSS helps reduce subjectivity and increase efficiency in the selection process. The research results show that based on the application of the OCRA method, the highest result among several alternatives is achieved by Ridho Permana with a score of 3.284. The OCRA method is effective in determining the best graphic designer candidate based on preference values calculated from various available alternatives. By applying the OCRA method, it is expected that the graphic designer selection process will become more objective and structured.